2018
DOI: 10.11648/j.cajph.20180405.12
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Smartphone Use Among Clinical Medical Students of Bingham University Teaching Hospital, Jos

Abstract: Background: Mobile phones are one of the most common information access devices with almost 31% of the global population having access. Mobile phones are now in the hands of 2 billion people out of the 6.47 billion people on this planet. The knowledge on the pattern of use of mobile phones among students will shed more light on the advantages and disadvantages of the use of mobile phones so as to find ways of channeling the usage into being more beneficial and useful to the students. The aim is to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
2
1
Order By: Relevance
“…While, based on the questions on knowledge about SDGs, we found that few students still lacked knowledge on basic information of SDGs such as the year it was launched, few agendas of SDGs and the organization which launched SDGs. However, the student knowledge result in this study is higher than the study from Shehu et al (2018) among clinical medical students and Omisore et al (2017) among University Community in Nigeria possibly because of the socio-demographic condition between the study area.…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…While, based on the questions on knowledge about SDGs, we found that few students still lacked knowledge on basic information of SDGs such as the year it was launched, few agendas of SDGs and the organization which launched SDGs. However, the student knowledge result in this study is higher than the study from Shehu et al (2018) among clinical medical students and Omisore et al (2017) among University Community in Nigeria possibly because of the socio-demographic condition between the study area.…”
Section: Resultscontrasting
confidence: 74%
“…It showed that female students had higher awareness such as 5.5% than male students. The previous studies by Shehu et al (2018) and Omisore et al (2017), differently, found with their female respondents being less aware of SDGs compared to the males. The different socio-demographic grounds and cultural expectations of gender roles might cause this inversed findings.…”
Section: Source: Spss Data Processingmentioning
confidence: 72%
See 1 more Smart Citation